Composite flame-retardant coating and preparation method thereof, and flame-retardant hydrogel coating and preparation method thereof
By preparing composite flame retardant coatings and applying them to the substrate surface, the problem of insufficient thermal stability and adhesion ability of hydrogel coatings is solved, and better carbon-forming performance and flame retardant performance are achieved, and are suitable for wood, foam and other fields.
Patent Information
- Application Number
- CN202411602917.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing hydrogel coatings have low thermal stability, insufficient carbon-forming function and adhesion capabilities, which limit their application.
The double bond-containing sulfonate monomer and the double bond-containing phosphate monomer are polymerized in the presence of a reinforcement, a crosslinking agent, a photoinitiator and water to obtain a precursor solution and mix it in contact with the filler to prepare a composite flame retardant coating. The composite coating is coated on the surface of the substrate and cured under ultraviolet light to form a flame retardant hydrogel coating.
The carbonization performance, adhesion and thermal stability of the hydrogel coating are improved, the fire resistance and secondary flame retardancy of the carbonized layer are enhanced, and the flame retardant fire resistance and heat insulation performance are significantly improved.
Smart Images

Figure CN119529618A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of new materials, and in particular to a composite flame retardant coating and a preparation method thereof, a flame retardant hydrogel coating and a preparation method thereof. Background Art
[0002] Rigid polyurethane foam (RPUF) has been widely used in various industries such as building exterior walls, pipe insulation and aerospace due to its excellent thermal insulation properties. However, it has a porous structure and a large specific surface area, which makes it very easy to burn. Once ignited, the flame will spread rapidly and produce a large amount of toxic gases, posing a significant fire hazard. In order to address the fire hazard of RPUF, efforts have been made to develop flame-retardant RPUF. Surface coating flame retardant technology is one of the promising alternatives, which can inhibit the spread of flames and provide fire protection by forming a thermally stable carbon layer without affecting the material properties.
[0003] Hydrogels are cross-linked polymer networks that can retain large amounts of water and maintain a 3D layered structure. Hydrogel coatings are considered to be green materials due to their high water content, high viscosity, and hydrophilicity. When exposed to flames or high temperatures, the water vapor within the hydrogel can effectively dissipate a large amount of heat, acting as an oxygen barrier, and can maintain a low temperature on the surface of the material before the water completely evaporates, hindering the combustion process. This unique property gives hydrogel coatings great potential as flame-retardant coatings. In addition, the addition of flame-retardant materials to hydrogels can reduce the heat transfer rate when char residues are produced, thereby suppressing fires; at the same time, it can prevent water loss and form a fire-resistant layer on the surface of the material. Therefore, hydrogel coatings have received increasing attention in polymer flame retardancy and have been used in rigid polyurethane foam materials with relatively ideal flame retardant effects.
[0004] However, the low thermal stability of hydrogels and the weak adhesion of the protective layer they form limit their applications. Therefore, we need to further improve the thermal stability, carbonization function and adhesion ability of hydrogel coatings.
[0005] CN 105348427A discloses a method for preparing a polymer sulfonate flame retardant, wherein the preparation method is to react an unsaturated sodium sulfonate monomer, an unsaturated potassium sulfonate monomer and a vinyl monomer by a free radical polymerization method to generate the polymer sulfonate, wherein the vinyl monomer is any one or more selected from C6-C12 aromatic vinyl compounds, (meth) acrylate compounds, vinyl amide compounds, vinyl ether compounds or cyano vinyl compounds. This technical solution solves the problems of conventional small molecule sulfonate flame retardants, such as strong hydrophilicity, easy hygroscopic deliquescence, easy migration of components, poor compatibility and difficulty in uniform dispersion, but it still has the defects of low flame retardant efficiency and poor smoke suppression effect. Summary of the invention
[0006] The purpose of the present invention is to solve the problems of poor adhesion, thermal stability and carbon-forming ability of the hydrogel coating in the prior art.
[0007] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a composite flame retardant coating, the method comprising:
[0008] (1) in the presence of an enhancer, a crosslinking agent, a photoinitiator and water, polymerizing a sulfonate monomer containing a double bond and a phosphate monomer containing a double bond to obtain a precursor solution;
[0009] (2) contacting and mixing the precursor solution and the filler to obtain the composite flame retardant coating;
[0010] Wherein, the weight ratio of the sulfonate monomer containing a double bond, the phosphate monomer containing a double bond and the filler is 1:0.2-10:0.1-0.5;
[0011] The filler is a fibrous filler and / or a layered filler, and the average diameter of the filler is 300-500 nm.
[0012] The second aspect of the present invention provides a composite flame retardant coating prepared by the method described in the first aspect.
[0013] A third aspect of the present invention provides a flame retardant hydrogel coating, which comprises a substrate and a composite flame retardant coating applied to the upper and lower surfaces of the substrate;
[0014] The composite flame retardant coating is the composite flame retardant coating described in the second aspect.
[0015] The fourth aspect of the present invention provides a method for preparing the flame retardant hydrogel coating according to the third aspect, the method comprising:
[0016] (1) applying the composite flame retardant coating to the upper and lower surfaces of the substrate to obtain an intermediate;
[0017] (2) curing the intermediate under ultraviolet light to obtain the flame retardant hydrogel coating.
[0018] Through the above technical solution, the present invention has at least the following advantages:
[0019] (1) The composite flame retardant coating prepared by the method for preparing a composite flame retardant coating provided by the present invention has better carbonization performance than ordinary hydrogel coating, and has strong adhesion to the substrate and is not easy to fall off. Therefore, the method not only enhances the strength of the hydrogel coating and ensures the excellent performance of the coating, but also further improves the fire resistance and secondary flame retardancy of the carbonized layer of the composite flame retardant coating.
[0020] (2) The composite flame retardant coating provided by the present invention has fire resistance, high temperature resistance, excellent charring performance, strong designability, etc., and can be widely used in the fields of wood, foam, forest fire prevention and fire extinguishing.
[0021] (3) When the composite flame retardant coating provided by the present invention is applied to the flame retardant hydrogel coating, during the combustion and pyrolysis process of the flame retardant hydrogel coating, water evaporates from the composite flame retardant coating applied to the substrate, which helps to reduce heat and dilute oxygen, thereby forming a carbon layer to prevent the transfer of heat and mass, reduce the surface temperature of the substrate, and improve the fire safety of the material. Therefore, without affecting the mechanical properties, the flame retardant hydrogel coating has significant flame retardant, fireproof and heat insulation properties.
[0022] (4) The flame retardant hydrogel coating provided by the present invention has good flame retardant effect, good thermal stability and heat insulation capacity, can prolong the time for the foam to be ignited, and has excellent smoke suppression effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a graph showing the adhesion data of the composite flame retardant coating prepared in Example 1 of the present invention applied to different substrates;
[0024] Figure 2 It is a heat release rate curve diagram of the flame retardant hydrogel coating prepared from the composite flame retardant coating of Examples 1-4 of the present invention and the untreated pure rigid polyurethane foam;
[0025] Figure 3 is a total smoke production curve of the flame retardant hydrogel coating prepared from the composite flame retardant coating of Examples 1-4 of the present invention and the untreated pure rigid polyurethane foam;
[0026] Figure 4 is a carbon monoxide production curve of the flame retardant hydrogel coating prepared from the composite flame retardant coating of Examples 1-4 of the present invention and the untreated pure rigid polyurethane foam;
[0027] Figure 5 It is a data chart of oxygen index and UL-94 grade of the flame retardant hydrogel coating prepared from the composite flame retardant coating of Examples 1-4 of the present invention and untreated pure rigid polyurethane foam. DETAILED DESCRIPTION
[0028] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0029] In the present invention, photoinitiator-1173 refers to 2-hydroxy-2-methyl-1-phenyl-1-propanone; photoinitiator-184 refers to hydroxycyclohexane phenone; and photoinitiator-2959 refers to 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropanone.
[0030] As mentioned above, the first aspect of the present invention provides a method for preparing a composite flame retardant coating, the method comprising:
[0031] (1) in the presence of an enhancer, a crosslinking agent, a photoinitiator and water, polymerizing a sulfonate monomer containing a double bond and a phosphate monomer containing a double bond to obtain a precursor solution;
[0032] (2) contacting and mixing the precursor solution and the filler to obtain the composite flame retardant coating;
[0033] Wherein, the weight ratio of the sulfonate monomer containing a double bond, the phosphate monomer containing a double bond and the filler is 1:0.2-10:0.1-0.5;
[0034] The filler is a fibrous filler and / or a layered filler, and the average diameter of the filler is 300-500 nm.
[0035] Preferably, the double bond-containing sulfonate monomer is selected from at least one of sodium vinyl sulfonate, sodium allyl sulfonate, sodium styrene sulfonate, potassium vinyl sulfonate and potassium 3-sulfonate propyl methacrylate, preferably at least one of sodium vinyl sulfonate, sodium allyl sulfonate, potassium vinyl sulfonate and potassium 3-sulfonate propyl methacrylate. The inventors have found that in this preferred case, the flame retardant and smoke suppression properties of the flame retardant hydrogel coating obtained by the technical solution provided by the present invention are more superior.
[0036] Preferably, the double bond-containing phosphate monomer is selected from 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate, triallyl phosphate, di[2-(methacryloyloxy)ethyl]phosphate, acrylic acid phosphate FM30 and acrylic phosphate At least one of FM20, preferably 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate, triallyl phosphate and acrylic acid phosphate At least one of FM30. In this preferred case, the flame retardant hydrogel coating obtained by the technical solution provided by the present invention has better flame retardant and smoke suppression performance.
[0037] Preferably, the weight ratio of the sulfonate monomer containing a double bond, the phosphate monomer containing a double bond and the filler is 1:0.5-1:0.25-0.3.
[0038] Preferably, the weight ratio of the double-bond-containing phosphate monomer to the enhancer is 1:0.1-1, preferably 1:0.1-0.2.
[0039] Preferably, the weight ratio of the reinforcing agent, the crosslinking agent and the photoinitiator is 1: 0.1-10: 0.001-1. In this preferred embodiment, the technical solution provided by the present invention can obtain a flame retardant hydrogel coating with better flame retardancy and smoke suppression.
[0040] Preferably, the weight ratio of the cross-linking agent to the water is 1:200-300.
[0041] Preferably, the fibrous filler is selected from at least one of cellulose fiber, silica fiber, alumina fiber and aramid fiber, preferably cellulose fiber and / or silica fiber.
[0042] Preferably, the layered filler is selected from at least one of black phosphorus sheets, graphene sheets, titanium carbide sheets, boron nitride sheets and clay, preferably black phosphorus sheets and / or boron nitride sheets.
[0043] Preferably, the enhancer is selected from at least one of acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, hydroxyethyl acrylate and 2-phenoxyethyl acrylate, preferably at least one of acrylamide, acrylic acid and hydroxyethyl acrylate.
[0044] Preferably, the cross-linking agent is selected from at least one of N,N'-methylenebisacrylamide, ethylene glycol diacrylate and hexamethylenebisacrylamide, preferably N,N'-methylenebisacrylamide and / or ethylene glycol diacrylate.
[0045] Preferably, the photoinitiator is selected from at least one of photoinitiator-1173, photoinitiator-184 and photoinitiator-2959, preferably photoinitiator-1173 and / or photoinitiator-2959.
[0046] Preferably, in step (1), the polymerization reaction conditions include: temperature of 25-60° C. and time of 0.5-1 h.
[0047] Preferably, in step (2), the contact mixing conditions include: temperature of 25-60° C. and time of 0.5-1 h.
[0048] As mentioned above, the second aspect of the present invention provides a composite flame retardant coating prepared by the method described in the first aspect.
[0049] As mentioned above, the third aspect of the present invention provides a flame retardant hydrogel coating, which comprises a substrate and a composite flame retardant coating applied to the upper and lower surfaces of the substrate;
[0050] The composite flame retardant coating is the composite flame retardant coating described in the second aspect.
[0051] As mentioned above, the fourth aspect of the present invention provides a method for preparing the flame retardant hydrogel coating according to the third aspect, the method comprising:
[0052] (1) applying the composite flame retardant coating to the upper and lower surfaces of the substrate to obtain an intermediate;
[0053] (2) curing the intermediate under ultraviolet light to obtain the flame retardant hydrogel coating.
[0054] Preferably, in step (1), the coating thickness is independently 0.1-5 mm / surface.
[0055] Preferably, in step (1), the substrate is a rigid polyurethane foam.
[0056] Preferably, in step (1), the coating method is selected from at least one of a brush coating method, a spray coating method and a dip coating method.
[0057] Preferably, in step (2), the curing treatment conditions include: a light intensity of 50-80 mW / cm 2 , wavelength is 300-400nm, and illumination time is 1-30min.
[0058] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the drugs and reagents used are all commercially available products.
[0059] Sodium vinyl sulfonate was purchased from Beijing Bailingwei Technology Co., Ltd., CAS No.: 3039-83-6.
[0060] Sodium allyl sulfonate was purchased from Shanghai Myrel Biochemical Technology Co., Ltd., CAS No.: 2495-39-8.
[0061] Sodium styrene sulfonate was purchased from Beijing Inokai Technology Co., Ltd., CAS No.: 2695-37-6.
[0062] Potassium 3-sulfonate propyl methacrylate was purchased from Beijing Yongchang Haoran Biotechnology Co., Ltd., CAS No.: 31098-21-2.
[0063] 2-Methyl-2-acrylic acid-2-hydroxyethyl ester phosphate was purchased from Beijing Xinbaohai Chemical Technology Co., Ltd., CAS No.: 52628-03-2.
[0064] Triallyl phosphate was purchased from Shanghai Jizhi Biochemical Technology Co., Ltd. CAS number: 1623-19-4.
[0065] In the following examples, acrylic acid phosphate FM30 is a mixture of acrylic acid monophosphate and acrylic acid diphosphate, the phosphate monomer is synthesized from O-(EO)n>10-CH3, and the active acrylic acid group is methacrylate; it was purchased from Beijing Baiyuan Chemical Co., Ltd.
[0066] The following examples are used to illustrate the method for preparing the composite flame retardant coating of the present invention.
[0067] Example 1
[0068] (1) in the presence of a reinforcing agent, a crosslinking agent, a photoinitiator and water, a sulfonate monomer containing a double bond and a phosphate monomer containing a double bond are uniformly stirred to perform a polymerization reaction (temperature is 25° C., time is 0.5 h), to obtain a precursor solution;
[0069] (2) The precursor solution and the filler are mixed evenly to perform contact mixing (temperature is 25° C., time is 1 h) to obtain a composite flame retardant coating.
[0070] The raw materials and proportions of the present embodiment are shown in Table 1.
[0071] Examples 2 to 4 are all prepared using the same preparation method as Example 1, except that the raw materials and their ratios are different, as shown in Table 1.
[0072] Table 1 (the amount of the double-bond phosphate monomer is 2 g, and the weight ratio of the enhancer, crosslinker and photoinitiator is 1:0.1:0.025)
[0073]
[0074] Example 5
[0075] This example is carried out in a similar manner to that of Example 1, except that the double-bond-containing sulfonate monomer in this example is replaced with sodium styrene sulfonate to obtain a composite flame-retardant coating.
[0076] Example 6
[0077] This example is carried out in a similar manner to that of Example 1, except that the double-bond-containing phosphate monomer of this example is replaced with di[2-(methacryloyloxy)ethyl]phosphate to obtain a composite flame-retardant coating.
[0078] Example 7
[0079] This example is carried out in a similar manner to Example 1, except that the amount of the reinforcing agent in this example is kept unchanged, and the weight ratio of the reinforcing agent, the crosslinking agent and the photoinitiator is adjusted to 1:0.05:0.025 to obtain a composite flame retardant coating.
[0080] Comparative Example 1
[0081] This comparative example is carried out in a similar manner to Example 1, except that the amount of the sulfonate monomer containing a double bond in this comparative example is kept unchanged, and the weight ratio of the sulfonate monomer containing a double bond, the phosphate monomer containing a double bond and the filler is adjusted to 1:0.1:1 to obtain a composite flame retardant coating.
[0082] Test Case
[0083] At room temperature, the adhesion of the composite flame retardant coating prepared in the example was tested when applied to different substrates such as polyurethane, glass, nylon (PA), polyvinyl chloride (PVC) and polymethyl methacrylate (PMMA). The peak data of the adhesion test are shown in Table 2.
[0084] Among them, the adhesion test method is as follows: ① Perform a lap shear test on the material in accordance with the ASTM F2255-05 (2015) standard. Before each test, carefully wipe off excess surface moisture with a paper towel; ② Cut the sample into a rectangular specimen of 4 cm (length) × 1.2 cm (width); ③ Place a hydrogel sample with a side length of 1.2 cm and a thickness of 2 mm on the side of the sample surface close to the endpoint; ④ Place another sample on the hydrogel sample to form a square overlapping area with a side length of 1.2 cm; ⑤ Perform a tensile test, and the force divided by the cross-sectional area is the adhesion.
[0085] Table 2
[0086]
[0087]
[0088] The present invention Figure 1 exemplarily provides a graph of the adhesion of the composite flame retardant coating prepared in Example 1 of the present invention to different substrates; Figure 1 It can be seen that the composite flame retardant coating prepared in Example 1 has strong adhesion to substrates such as polyurethane, glass, nylon (PA), polyvinyl chloride (PVC) and polymethyl methacrylate (PMMA).
[0089] The following application examples are used to illustrate the method for preparing a flame retardant hydrogel coating of the present invention.
[0090] Application Example 1
[0091] (1) The composite flame retardant coating prepared in Example 1 was evenly applied to the upper and lower surfaces of a substrate (rigid polyurethane foam) by brushing, with a coating thickness of 1 mm / surface, to obtain an intermediate.
[0092] (2) Keep the intermediate body horizontal and cure it under ultraviolet light (light intensity is 80 mW / cm 2 , wavelength of 365nm, illumination time of 1min) to obtain a flame retardant hydrogel coating.
[0093] Application Examples 2 to 7
[0094] The method of Application Example 1 is followed, except that the composite flame retardant coatings prepared in Examples 2 to 7 are used to replace the composite flame retardant coating prepared in Example 1.
[0095] Flame retardant hydrogel coatings were obtained respectively.
[0096] Comparative Application Example 1 to Comparative Application Example 2
[0097] The method of Application Example 1 is followed, except that the composite flame retardant coatings prepared in Comparative Examples 1 and 2 are used to replace the composite flame retardant coating prepared in Example 1.
[0098] Flame retardant hydrogel coatings were obtained respectively.
[0099] Application test case
[0100] The flame retardant hydrogel coating prepared in the corresponding example was subjected to performance tests, including heat release rate, total smoke production, carbon monoxide production, limiting oxygen index (LOI) and UL-94 grade, and the above test results were compared with the test results of untreated pure rigid polyurethane foam. The test results are shown in Table 3.
[0101] Among them, the relevant test methods are as follows:
[0102] Heat release rate, total smoke production, and carbon monoxide production: According to ASTM E1354 / ISO 5660, the combustion performance of the material was tested and evaluated using a cone calorimeter (Fire Testing Technology, UK). The standard sample of the material (100×100×3mm 3 ) is wrapped in aluminum foil and placed on the sample stage of the calorimeter for combustion testing. The radiation flux is usually set to 35kW / m 2 .
[0103] Limiting oxygen index (LOl): The limiting oxygen index (LOl) is measured by HC-2 oxygen index instrument (Jiangning Analytical Instrument Factory), the sample size is 100mm×6.5mm×3.2mm, and the test standard is based on standard ASTM D2863.
[0104] UL-94 level: The vertical burning test (UL-94) is carried out on a CFZ-2 horizontal vertical burning tester (Jiangning Analytical Instrument Factory), with the sample size of 130.0mm×13.0mm×3.2mm and 130.0mm×13.0mm×1.6mm. The test standard is based on ASTM D3801.
[0105] Table 3
[0106]
[0107]
[0108] The present invention Figure 2 illustratively provides heat release rate curves of flame retardant hydrogel coatings prepared from composite flame retardant coatings of Examples 1-4 of the present invention and untreated pure rigid polyurethane foam, wherein pure foam refers to pure rigid polyurethane foam; Figure 2 It can be seen that the peak heat release rate of the flame retardant hydrogel coating prepared in Example 1-4 is 200-300 kW / m 2 The peak heat release rate of untreated pure rigid polyurethane foam is 450kW / m 2 This shows that the flame retardant hydrogel coating provided by the present invention exhibits good flame retardant properties.
[0109] The present invention Figure 3 exemplarily provides a total smoke production curve of the flame retardant hydrogel coating prepared by the composite flame retardant coating of Examples 1-4 of the present invention and the untreated pure rigid polyurethane foam, wherein the pure foam refers to the pure rigid polyurethane foam; Figure 3 It can be seen that the total smoke generation of the flame retardant hydrogel coatings prepared in Example 1-4 is between 4 and 5 m 2 The total smoke production of untreated pure rigid polyurethane foam is nearly 8m 2 This indicates that the flame retardant hydrogel coating provided by the present invention exhibits good smoke suppression performance.
[0110] The present invention Figure 4 exemplarily provides a carbon monoxide production curve of the flame retardant hydrogel coating prepared by the composite flame retardant coating of Examples 1-4 of the present invention and the untreated pure rigid polyurethane foam, wherein the pure foam refers to the pure rigid polyurethane foam; Figure 4 It can be seen that the carbon monoxide production of the flame retardant hydrogel coatings prepared in Application Examples 1-4 is between 0.004-0.005 g / s, while the carbon monoxide production of pure rigid polyurethane foam exceeds 0.008 g / s. This shows that the flame retardant hydrogel coating provided by the present invention exhibits good smoke suppression and toxicity reduction performance.
[0111] The present invention Figure 5 illustratively provides oxygen index and UL-94 grade data of flame retardant hydrogel coatings prepared from composite flame retardant coatings of Examples 1-4 of the present invention and untreated pure rigid polyurethane foam, wherein pure foam refers to pure rigid polyurethane foam; Figure 5 It can be seen that the flame retardant hydrogel coatings prepared in Application Examples 1-4 all reach the UL-94 V0 level, and the oxygen index exceeds 34%, while the pure rigid polyurethane foam has no level in the UL-94 test, and the oxygen index does not exceed 20%. This shows that the flame retardant hydrogel coating provided by the present invention exhibits good flame retardant and smoke suppression properties.
[0112] It can be seen from the above results that the composite flame retardant coating prepared by the method for preparing a composite flame retardant coating provided by the present invention has strong fire resistance and high temperature resistance, and its charring performance is superior to that of ordinary hydrogel coatings, and it has the characteristics of strong designability;
[0113] At the same time, the composite flame retardant coating has strong adhesion to the substrate, ensuring the excellent performance of the flame retardant hydrogel coating, enhancing the strength of the flame retardant hydrogel coating, and further improving the fire resistance and secondary flame retardancy of the carbonized layer, so that the flame retardant hydrogel coating can be widely used in wood, foam and forest fire prevention and fire fighting.
[0114] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a composite flame retardant coating, characterized in that: The method includes: (1) in the presence of an enhancer, a crosslinking agent, a photoinitiator and water, polymerizing a sulfonate monomer containing a double bond and a phosphate monomer containing a double bond to obtain a precursor solution; (2) contacting and mixing the precursor solution and the filler to obtain the composite flame retardant coating; Wherein, the weight ratio of the sulfonate monomer containing a double bond, the phosphate monomer containing a double bond and the filler is 1:0.2-10:0.1-0.5; The filler is a fibrous filler and / or a layered filler, and the average diameter of the filler is 300-500 nm.
2. The method according to claim 1, wherein: The double bond-containing sulfonate monomer is selected from at least one of sodium vinyl sulfonate, sodium allyl sulfonate, sodium styrene sulfonate, potassium vinyl sulfonate and potassium 3-sulfonate propyl methacrylate.
3. The method according to claim 1, wherein: The double-bond-containing phosphate monomer is selected from 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate, triallyl phosphate, di[2-(methacryloyloxy)ethyl]phosphate, acrylic acid phosphate FM30 and acrylic phosphate At least one of FM20.
4. The method according to any one of claims 1 to 3, wherein: The weight ratio of the double-bond-containing phosphate monomer to the enhancer is 1:0.1-1; and / or, the weight ratio of the reinforcing agent, the crosslinking agent and the photoinitiator is 1:0.1-10:0.001-1; And / or, the weight ratio of the cross-linking agent to the water is 1:200-300.
5. The method according to any one of claims 1 to 3, wherein: The fibrous filler is selected from at least one of cellulose fiber, silica fiber, alumina fiber and aramid fiber; And / or, the layered filler is selected from at least one of black phosphorus sheets, graphene sheets, titanium carbide sheets, boron nitride sheets and clay; and / or, the enhancer is selected from at least one of acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, hydroxyethyl acrylate and 2-phenoxyethyl acrylate; and / or, the cross-linking agent is selected from at least one of N,N'-methylenebisacrylamide, ethylene glycol diacrylate and hexamethylenebisacrylamide; And / or, the photoinitiator is selected from at least one of photoinitiator-1173, photoinitiator-184 and photoinitiator-2959.
6. A composite flame retardant coating prepared by the method according to any one of claims 1 to 5.
7. A flame retardant hydrogel coating, characterized in that: The flame retardant hydrogel coating comprises a substrate and a composite flame retardant coating applied to the upper and lower surfaces of the substrate; The composite flame retardant coating is the composite flame retardant coating according to claim 6.
8. A method for preparing the flame retardant hydrogel coating according to claim 7, characterized in that: The method includes: (1) applying the composite flame retardant coating to the upper and lower surfaces of the substrate to obtain an intermediate; (2) curing the intermediate under ultraviolet light to obtain the flame retardant hydrogel coating.
9. The method according to claim 8, wherein: In step (1), the coating thickness is independently 0.1-5 mm / surface; And / or, the substrate is rigid polyurethane foam.
10. The method according to claim 8 or 9, wherein: In step (2), the curing treatment conditions include: the light intensity is 50-80mW / cm 2 , wavelength is 300-400nm, and illumination time is 1-30min.
Citation Information
Patent Citations
Polymer sulfonate fire retardant, and preparation method as well as application thereof
CN105348427A